The secrets of Buddhist meditation visionary meditation texts from early medieval China - Greene, Eric Matthew (University of Hawai'i Press, 2021)
This volume presents a comprehensive study of the content and historical formation, as well as complete English translations, of two of the most influential manuals in which these approaches to Buddhist meditation are discussed: the Scripture on the Secret Essential Methods of Chan (Chan Essentials) and the Secret Methods for Curing Chan Sickness (Methods for Curing).Translated here into English for the first time, these documents reveal a distinctly visionary form of Buddhist meditation whose goal is the acquisition of concrete, symbolic visions attesting to the practitioner's purity and progress toward liberation. Both texts are "apocryphal" scriptures: Taking the form of Indian Buddhist sutras translated into Chinese, they were in fact new compositions, written or at least assembled in China in the first half of the fifth century.
Keywords: Geschichte 400-500; RELIGION / Buddhism / Sacred Writings / bisacsh; Meditation -- Buddhism; Buddhismus; Meditation; China; Quelle